2004
DOI: 10.1890/04-0003
|View full text |Cite
|
Sign up to set email alerts
|

Insect Canopy Herbivory and Frass Deposition Affect Soil Nutrient Dynamics and Export in Oak Mesocosms

Abstract: Increased nitrogen (N) mobilization and export from terrestrial forest ecosystems following canopy herbivory have been well documented, though the mechanism behind the loss is not clear. Because carbon (C) and N dynamics are closely linked, herbivore activity may also affect C distribution. We initiated a replicated mini-ecosystem experiment to test the hypothesis that insect frass (feces) influences soil C and N dynamics following insect defoliation. One hundred and sixty red oak (Quercus rubra) saplings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
146
3
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(160 citation statements)
references
References 75 publications
(144 reference statements)
9
146
3
2
Order By: Relevance
“…This study in forest plots which have undergone almost complete defoliation in a relatively unproductive ecosystem (Myneni and others 2001;Karlsen and others 2008) shows the opposite response to more productive ecosystems, which experienced a smaller reduction in belowground C allocation. In a temperate deciduous system, belowground respiration rates increased in response to relatively mild defoliation (8% less foliage than control; (Frost and Hunter 2004)). This was similar to patterns of increased C allocation belowground by plants in response to partial Here the authors explained the increase in C flux as being due to a combination of increased root growth, turnover, activity and labile C input, all as mechanisms to recover N that was lost from leaf biomass (Frost and Hunter 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study in forest plots which have undergone almost complete defoliation in a relatively unproductive ecosystem (Myneni and others 2001;Karlsen and others 2008) shows the opposite response to more productive ecosystems, which experienced a smaller reduction in belowground C allocation. In a temperate deciduous system, belowground respiration rates increased in response to relatively mild defoliation (8% less foliage than control; (Frost and Hunter 2004)). This was similar to patterns of increased C allocation belowground by plants in response to partial Here the authors explained the increase in C flux as being due to a combination of increased root growth, turnover, activity and labile C input, all as mechanisms to recover N that was lost from leaf biomass (Frost and Hunter 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In a temperate deciduous system, belowground respiration rates increased in response to relatively mild defoliation (8% less foliage than control; (Frost and Hunter 2004)). This was similar to patterns of increased C allocation belowground by plants in response to partial Here the authors explained the increase in C flux as being due to a combination of increased root growth, turnover, activity and labile C input, all as mechanisms to recover N that was lost from leaf biomass (Frost and Hunter 2004). All of these processes depend on a high flux of autotrophic C to maintain roots and associated mycorrhizal symbionts (Litton and others 2007;Ekblad and others 2013;Brzostek and others 2015); something that was not possible in the present study as the defoliated trees suffered almost complete defoliation.…”
Section: Discussionmentioning
confidence: 99%
“…Because the growth of soil organisms is generally controlled by carbon availability (Bardgett and Wardle 2010), a major reduction of carbon flux belowground, such as the removal of canopy foliage due to herbivory, is likely to have a marked impact on soilinhabiting organisms. Intensive moth herbivory on tree canopies results in massive deposition of moth feces (frass) with high quantities of dissolved N and C compounds into the soil (Frost and Hunter 2004). Canopy herbivory has been found to change understory plant community composition as well as alter litter input and quality (Wardle et al 2004, Mitchell et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is suggested that DOM input with throughfall is a leading promoter for decomposition processes in the forest floor, significantly affecting the C partitioning of the litter input into CO 2 , DOC and humic material and its fate in the mineral soil (Madritch and Hunter 2003;Chapman et al 2003: Frost andHunter 2004).…”
mentioning
confidence: 99%